PELAKSANAAN HAK ISTERI DAN ANAK ATAS GAJI PEGAWAI NEGERI SIPIL AKIBAT PERCERAIAN - Remon Egle (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTTechnical implementation rather than the rights of the ex- wife of her husband's former salary , salary division when the divorce was due to the will of the male civil servants salary divided as follows Legal consequences of divorce are as follows : At the level ba'in talaq , divorce is talaq which has entered level three where the couple is forbidden to reconcile his ex-wife before marrying another person prior to that person later divorced ; Divorce for li ' s, then the marriage can no longer be done for ever ; Treasure joint wealth is shared between husband and wife while the cost of maintenance and education is the responsibility of the father . More entitled to maintain his children are his mother , for the mother was married to someone else .